A retenção de talentos dos profissionais de tecnologia da informação à luz da experiência do empregado: uma proposição de artefato - Santos, Sabrina Kassick (Universidade do Vale do Rio dos Sinos, 2023)
The Information Technology (IT) sector is currently competing for its talents. In Brazil, not even the layoffs carried by global big techs changed this. Literature demonstrates that in order to attract and retain such talents, organizations should rethink and improve their employee experience. Thus, the Morgan model was adopted in this research to propose a dashboard for the employee experience of contractors in the South American IT team of a global company. The method adopted by the researcher was the design science research (DSR). Firstly, the original Morgan questionnaire was statistically validated. From this validation resulted a 12-affirmative questionnaire in Portuguese, organized in the three dimensions of Morgan. The validated instrument was then made available to all 107 professionals part of the South American IT team in a global company. The region reached a score of 84% in its employee experience, which classifies it as an experienced company. Following the DSR suggestion and development phases, a dashboard was proposed as the artifact resulting from the metod application. In the evaluation phase, the dashboard was validated by two steps: a focus group and its practical application for a period of one month. The final and validated version of the dashboard presents three stages of the employee experience designed for the researched organization: integration, follow-up and offboarding. Theoretical and practical contributions of this research are the increase in academic production on employee experience for the brazilian scenario, the validation of an instrument to measure employee experience and the improvement of people management by the adoption of an employee experience dashboard.
Keywords: Retenção de talentos; Experiência do empregado; Modelo de Morgan; Validação estatística de instrumento; Painel de gestão; Talent retention; Employee experience; Morgan EX model; Statistical validation of instrument; Management dashboard; ACCNPQ::Ciências Sociais Aplicadas::Administração